Resistance of Echinochloa crus-galli Populations to Acetolactate Synthase-Inhibiting Herbicides - Dilpreet S. Riar; Jason K. Norsworthy; Jason A. Bond; Mohammad T. Bararpour; Michael J. Wilson; Robert C. Scott (International Journal of Agronomy)
Three Echinochloa crus-galli (barnyardgrass) populations from rice fields in Arkansas (AR1 and AR2) and Mississippi (MS1), USA, were recently confirmed to be resistant to imazethapyr. Experiments were conducted to characterize cross-resistance to acetolactate synthase- (ALS-) inhibiting herbicides and determine if malathion, a known cytochrome P450 monooxygenase (CYP) inhibitor, would overcome resistance. The AR1 and MS1 populations were cross-resistant to bispyribac-sodium; however, AR2 was sensitive to bispyribac-sodium. The AR1, AR2, and MS1 populations were >94, >94, and 3.3 times, respectively, more resistant to imazamox; >94, 30, and 9.4 times, respectively, more resistant to penoxsulam; and 15, 0.9, and 7.2 times, respectively, more resistant to bispyribac-sodium compared to a susceptible population. Addition of malathion to penoxsulam reduced dry weight of all populations and increased mortality of AR2 and MS1 populations compared to penoxsulam alone. Addition of malathion to imazethapyr and bispyribac-sodium increased the mortality of MS1 population in mixture with imazethapyr and AR1 population in mixture with bispyribac-sodium compared to treatments with imazethapyr and bispyribac-sodium applied alone. Synergism of ALS-inhibiting herbicides with malathion indicates increased herbicide degradation by CYP as partial mechanism of resistance to penoxsulam in all resistant populations and probably to imazethapyr in MS1 and bispyribac-sodium in AR1 populations.